(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Our trial aims at investigating the impact performed by the mixture of a growing-regulator and fungicides upon summer rape productivity, the crop structure, and quality, to justify applying of agrochemicals in smaller doses thus eliminating environment pollution and winning labour-saving resource and financial applying per unit of sowing- fields, and per unit of the gained production. In 2001 – 2003, Research institute of Agriculture preparations during the trial were tested applying half doses (0,5 1 ha–1), creating the preparation mixtures: Moddus+ Folicur, Modus + Juventus; Cycocel + Folicur Cycocel + Juventus, through spraying them throughout plant florescence-bud formation (GS 50). Owing to the mixtures of preparations, the number of side branches increased, on average, for 1-2, the number of legumes on a plant – for 22-25, the number of seeds per legume for 2- 4, the mass o f 1000 seeds: from 3,7 to 4,2 g, at the same time the length of rape”s stem”s shorted down to 10-20 cm, and the branching height to 5-14 cm. The highest efficiency, however, was reached when applying the mixture of Cycocel and Juventus.On average, throughout all the three years, thanks to applying of growing-regulators and fungicides the summer oilseed rape harvesting essentially increased, if compared to the Control. The increase of harvest was 0,53-0,81 t ha –1 (γ0,05 0,24 t ha-1). During the trial-years the very best preparation mixture was nominated, and it was the Cycocel + Juventus, which, on average, provided the seed harvest 3,31 t ha –1, and the oil output 1409 kg ha –1. Other mixtures ensured a related seed output – 3,03-3,15 t ha –1, and the oil output 1270-1302 kg ha–1.